Heterogeneity in households' expectations of housing prices: Evidence from micro data - Erik Hjalmarsson; Pär Österholm (Sveriges Riksbank, 2019)
Expectations about future housing prices are arguably an important determinant of actual housing prices, and an important input in decisions on whether and how to transact in the housing market. Using novel micro-level survey data on Swedish households, we analyse households' expectations of housing prices and how these expectations relate to the characteristics of the respondents. Results show that age is significantly related to housing-price expectations, with the youngest households - whose adulthood largely corresponds to the extended period of rapid housing-price growth in Sweden - having the highest housing-price expectations, thus lending support to the hypothesis that expectations are influenced by personal experiences. Our findings suggest that aggregate measures of expectations might hide important features of the data, which could be of interest to policy makers when choosing regulatory actions or formulating macroprudential policies.
Keywords: G41; R20; 330; Housing prices; Survey data